Global Bonding : Do U.S. Bond and Equity Spillovers Dominate Global Financial Markets? - Bayoumi, Tamim (IMF Working Papers; Working Paper ;, 2012)
This paper uses a novel variant of identification through hetroscedacity to estimate spillovers across U.S., Euro area, Japanese, and UK government bond and equity markets in a vector autoregression. The results suggest that U.S. financial shocks reverberate around the world much more strongly than shocks from other regions, including the Euro area, while inward spillovers to the U.S. from elsewhere are minimal. There is also evidence of two-way spillovers between the UK and Euro area financial markets and spillovers from Europe to Japan. The results also suggest that the uncertainty about the direction of causality of contemporaneous correlations-an issue that other techniques cannot tackle-is the dominant source of uncertainty in the estimated impulse response functions.